Influence of target width and distance on postural adjustments in a fencing lunge - Akbas, A.; Marszalek, W.; Brachman, A.; Juras, G. (Journal of Human Kinetics, 2023)
The aim of this study was to examine whether target width and target distance influence the planning phase of a fencing lunge (early and anticipatory postural adjustments) as well as the execution phase of a fencing lunge. Eight elite female fencers participated in the study. The displacement of the center of foot pressure, muscle activity of the tibialis anterior, and kinematics of center of mass were recorded using force plates. The results show that target width and distance have no effect on early and anticipatory postural adjustments as well as the acceleration and velocity of the center of mass at the moment of foot-off. However, a greater target distance was associated with a greater max center of mass acceleration and velocity, and larger target width resulted in a greater max center of mass acceleration during lunging (p < 0.05). We suppose that the effect of task parameters on preparing a fencing lunge may be mitigated due to the specific technique adopted by expert fencers and the ballistic nature of a fencing lunge.